Learn to program ebook - Lyons, Heather (Kids Get Coding., 2016)
What do programs tell computers to do? And how are they written? Programs are instructions that computers follow. Learn about different programming languages, coding rules and bugs, and how to solve problems. Once you know the basics about computer programming, use the link in this book to go online and try out your new skills! Self-directed projects and activities help kids learn the basics of coding. What's an algorithm? How do you fix bugs? What is an app? How do you program a computer game? The Kids Get Coding series leads students through the basics of computer programming using real-world examples and practical activities.